Rumor has it - Mansell, Jill. (Naperville, Ill. : Sourcebooks Landmark, 2010)
Newly single, Tilly impulsively accepts a job in a small town. She soon finds herself in a hotbed of gossip, intrigue, and rampant rivalry for Jack, the town's most desirable bachelor. She decides to do the sensible thing, and avoid him at all costs.
Originally published: London : Headline Review, 2009.
Keywords: Single women -- Fiction; Mate selection -- Fiction; City and town life -- England -- Fiction; Man-woman relationships -- Fiction; Romance fiction